Effect of Green Tea Extract Supplementation and Impact of Catechol-O-Methyltransferase Genotype on Plasma Concentration of F2-Isoprostanes in Women Who Are Post-menopause. (14th June 2022) - Bathgate, Jennifer; Radler, Diane Rigassio; Gross, Myron; Kurzer, Mindy; Samavat, Hamed
Abstract: Objectives: Green tea extract (GTE) is a potential mitigator of oxidative stress. F2 -isoprostanes are a reliable and easily measured marker of oxidative stress. Genetic polymorphisms in the catechol-o-methyltransferase ( COMT ) gene may modify green tea catechin metabolism and potentially prolong exposure to catechins in those with lower activity COMT genotypes. The objective of this study was to assess if GTE supplementation would result in a decrease in plasma F2 -isoprostanes concentration as compared to placebo. A secondary objective was to determine the impact of the COMT genotype on F2 -isoprostanes concentration among participants receiving GTE. Methods: This study is a secondary analysis of the Minnesota Green Tea Trial (MGTT), a randomized placebo-controlled, double-blinded trial investigating the effects of GTE in nearly 1000 women who were generally healthy and post-menopause. The treatment group consumed 843 mg of epigallocatechin gallate daily for 12 months as two capsules twice daily, vs identically appearing placebo capsules for controls. The current analysis was conducted using data from the 254 participants who had plasma F2 -isoprostanes analyzed by a validated gas chromatography-mass spectrometry method. Results: The mean values of age and BMI were 59.7 years and 25.1 kg/m 2, respectively, and more than 96% of the women were non-Hispanic white. Using ANCOVA model adjusting for dietary protein intake there was no statistically significant difference in plasma F2 -isoprostanes concentrations between participants in the GTE ( n  = 133) as compared with the placebo group ( n  = 125) after 12 months ( P  = 0.557). There were no significant interactions between treatment and age, or BMI, physical activity, smoking history and alcohol intake. Additionally, COMT genotype did not modify the effect of GTE supplementation on F2 -isoprostanes concentration in those who consumed GTE supplement ( P  = 0.603). Conclusions: Among participants in the MGTT who were 50–70 years old and post-menopause, consuming GTE supplements daily for one year did not result in a significant decrease in plasma F2 -isoprostanes concentration, a biomarker of oxidative stress. Likewise, COMT genotype did not modify the effect of GTE supplementation on F2 -isoprostanes concentration. Funding Sources: NIH/NCI (Grant R01 CA127236).